2020
DOI: 10.1016/j.wroa.2020.100073
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic testing of flocculants for produced water treatment: Comparison with other methodologies

Abstract: Flocculants are often added during produced water treatment to improve the crude oil droplet growth and separation from the water phase. Prior to use in the field, their performance is tested in laboratory conditions, typically with jar tests that require quite large volumes of sample. In this paper we present a microfluidic method as an alternative to study the efficiency of flocculants on enhancing coalescence between oil droplets. Two crude oil emulsions and four flocculants at different concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…85−87 However, in PW systems, polymeric flocculants are more popular. 88 It has also been widely reported that the electrolyte concentration affects bubble sizes. 50,89−92 Furthermore, it has been demonstrated that the gas bubbles become much smaller above a certain critical salinity concentration, leading to more efficient gas dispersion.…”
Section: Water Composition 3221 Dissolved Organics In Pwmentioning
confidence: 98%
See 1 more Smart Citation
“…85−87 However, in PW systems, polymeric flocculants are more popular. 88 It has also been widely reported that the electrolyte concentration affects bubble sizes. 50,89−92 Furthermore, it has been demonstrated that the gas bubbles become much smaller above a certain critical salinity concentration, leading to more efficient gas dispersion.…”
Section: Water Composition 3221 Dissolved Organics In Pwmentioning
confidence: 98%
“…To promote droplet–droplet coalescence, coagulants containing the trivalent ions Al 3+ and Fe 3+ can be added to the system. However, in PW systems, polymeric flocculants are more popular …”
Section: Microscopic Aspects Of Gas Flotationmentioning
confidence: 99%
“…Similarly, Allison and Mandler [4] stated that on the average, 10 barrels of wastewater is generated for each barrel of crude oil processed. These large volumes of wastewater produced during petroleum production is either discharged into the sea or re-injected into production or disposal reservoirs [15] or for reuse purposes. The contaminants in the produced water are harmful to human, plants, animals [16] as well as public health and the environment are threatened by its presence [17].…”
Section: Significant Of Crude Oil Processed Water On the Environmentmentioning
confidence: 99%
“…Subsequent to droplet generation in microfluidics, the various types of downstream droplet interaction are numerous and often the end goal of a microfluidic experiment, depending on the application. In most of our previous reports [51,65], we focused on their coalescence or generally the interactions with other droplets. Here, we will showcase the analysis capabilities and symmetry to prior techniques using various CNNs on systems of freely flowing droplets, where the average diameter is smaller than the relatively large width (approximately 500 µm) of non-constrained flow cells.…”
Section: Flow Cellsmentioning
confidence: 99%